Analysis of Micro Teaching Course Implementation to Improve 8 Basic Teaching Skills for Accounting Education Students - Bunga Amanda; Dhany Efita Sari; Tarahilta Tarahilta (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The aim of this study is to describe the implementation of micro teaching in improving 8 basic teaching skills for future students in the accounting education course and to describe the constraints that accounting students experience during the implementation of the practice of micro teaching. The data processing technique in this study using the interactive analysis miles and huberman, which was afterward analyzed using the NVivo 12 applications. These findings include the following: (1) accounting education students are able to perform the practice of micro teaching with 8 teaching skills, (2) micro teaching was able to raise public speaking accounting education (3) micro teaching was able to provide teaching pictures to accounting education students before going directly into the field, (4) micro teaching was able to enhance communication skills for accounting students, And (5) through practice micro teaching can enhance students' creativity in choosing both learning and media strategies. The study was carried out to see if performing micro teaching in accounting education could improve student teaching skills to prepare students as prospective teachers.